Dysregulation of the renin-angiotensin system during lung ischemia-reperfusion injury. (2nd July 2016) - Kehoe, K.; Gielis, J. F.; Vliegen, G.; Van Elzen, R.; Verkerk, R.; Driessens, E.; Domen, A.; Lambeir, A. M.; Maes, L.; Cos, P.; De Meester, I.; Van Schil, P. E. Y.
ABSTRACT: Aim/Purpose of the Study: Activation of the renin-angiotensin system leading to increased angiotensin-(1–7) (Ang-(1–7)) and decreased angiotensin 2 (Ang 2) levels may be a new therapeutic approach to reduce acute lung injury. Prolylcarboxypeptidase (PRCP) and prolyloligopeptidase (PREP) are capable of hydrolyzing Ang 2 into Ang-(1–7). However, their relation with circulating Ang 2 levels after lung ischemia–reperfusion injury (LIRI) has never been explored. This study determines whether the activity and expression of PRCP and PREP in plasma and lung tissue is related to circulating Ang 2 levels in a murine model of LIRI.Materials and Methods: LIRI in Swiss mice (6 animals per group) was induced by temporary left lung hilar clamping (1 h) followed by 0, 1 or 24 h of reperfusion. Animals in the sham group received thoracotomy only. PRCP activity was measured via RP-HPLC, PREP activity using a fluorogenic substrate and plasma Ang 2 levels via ELISA. Western blotting was used to determine the PRCP and PREP protein expression profiles in left lung tissue.Results: Plasma Ang 2 levels significantly rise after lung ischemia and remain increased after 1 h and 24 h of reperfusion compared to the sham group. While a significant decrease in plasma PREP activity was found after 24 h of reperfusion, a transient increase in plasma PRCP activity was observed after ischemia. However, no correlation with plasma Ang 2 levels could be demonstrated. The activity profiles of PRCP and PREP and the protein expression of PRCP in the lung tissues remained unchanged after LIRI.Conclusions: LIRI causes a dysregulation of circulating Ang 2 levels and plasma PREP activity, although no direct link between both phenomena could be shown. The activity profile of pulmonary PRCP and PREP was not significantly changed after LIRI, which implies a minor role for local PRCP and PREP in the ischemic lung itself.